Exploring the Valorization of Buckwheat Waste: A Two-Stage Thermo-Chemical Process for the Production of Saccharides and Biochar - Yongheng Yuan; Faqinwei Li; Nanding Han; Bingyao Zeng; Yoshiaki Imaizumi; Risu Na; Naoto Shimizu (Fermentation, 2022)
To realize the utilization of the valorization of buckwheat waste (BW), a two-stage thermal-chemical process was explored and evaluated to produce saccharides and biochar. During the first stage, BW underwent a hydrothermal extraction (HTE) of varying severity to explore the feasibility of saccharides production; then, the sum of saccharides yields in the liquid sample were compared. A higher sum of saccharides yields of 4.10% was obtained at a relatively lower severity factor (SF) of 3.24 with a byproducts yield of 1.92 %. During the second stage, the contents of cellulose, hemicellulose, and lignin were analyzed in the residue after HTE. Enzymatic hydrolysis from the residue of HTE was inhibited. Thus, enzymatic hydrolysis for saccharides is not suitable for utilizing the residue after HTE of BW. These residues with an SF of 3.24 were treated by pyrolysis to produce biochar, providing a higher biochar yield of 34.45 % and a higher adsorption ability (based on methyl orange) of 31.11 % compared with pyrolysis of the raw BW. Meanwhile, the surface morphology and biomass conversion were analyzed in this study. These results demonstrate that the two-stage thermal-chemical process is efficient for treating BW and producing saccharides and biochar. This work lays a foundation for the industrial application of BW, and for improving the economic benefits of buckwheat cultivation.